Análise das inter-relações entre satisfação residencial e características da habitação sob as percepções do morador - Tortato, Larissa Araujo Soares (2024)
The field of study of residential satisfaction meets sustainability of urban life. In this area, personal, subjective and objective issues are considered, from physical characteristics of the residence and neighborhood to the person’s way of life and its customs. The objective of this research is to widen the understanding of the characteristics of single-family homes and their surroundings in relation to satisfaction. The research adopted the inductive method with a systemic view of the problem. The Survey was used as the basic research procedure and multivariate analysis as the statistical tool. Based on the bibliographical review of the topic, a questionnaire was prepared, the resulting data of which were analyzed using multivariate statistical techniques. It has been elucidated relationships between the resident and their residential environment, by identifying sets of relationships between variables (and group of variables). Among the most significant are the correlations between the housing recommendation and the resident’s opinion about the general size of the house, opinion about the internal space, opinion about circulation between rooms and opinion about the quality of the facade materials.